FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PADA BANK SYARIAH DI INDONESIA - Yurike Sofiana Askurun; Andriani (WADIAH, 2021)
Profitability is the most appropriate indicator to measure the performanceof a company. The company's ability to generate profits to measure thelevel of performance of a company. The higher the company's profitability,the better the company's performance. The purpose of this study was todetermine the effect of Financing Deposit Ratio (FDR), OEOI, CapitalAdequacy Ratio (CAR), and Non Performing Financing (NPF) onprofitability (ROA) of Islamic bank financial statements published byIndonesian banks. in the period 2008-2012.This study aims to analyze the effect of the FDR ratio, operationalefficiency (ROA), CAR, and NPF on profitability (ROA) in Islamic banks onpublished finances. Bank Indonesia, while the research sample wasdetermined by purposive sampling method in order to obtain 41 samplesfrom 11 banking companies during the observation period (2009-2012).The type of data used is secondary data obtained from Islamic bankfinancial statements at PT www.bi.go.id.The analytical method used is multiple regression analysis. The results ofthis study indicate that FDR has no significant effect on Indonesian Islamicbanks, BOPO has a significant effect on ROA in Islamic banks inIndonesia, CAR does not have a significant effect on Islamic banks inIndonesia, NPF has no significant effect on Indonesian Islamic banks.